Analysis of Water Deficit Indicators and Their Environmental Impacts in Baiji District (1993-2024) Using Geomatics Techniques - Louis, Mohammed Abed; Hammad, Luay Maher (Journal of Tikrit University for Humanities, 2025)
Water deficit is one of the most critical environmental challenges affecting ecological balance and agricultural systems in arid and semi-arid regions, such as Baiji in Iraq. The impact of water deficit depends on the soil’s ability to retain essential moisture to support agricultural activities and ecosystems. This study aimed to monitor soil vitality and efficiency in Baiji by analyzing satellite images and spectral data to detect soil changes and their effects on agricultural productivity and vegetation cover. A set of spectral indices derived from remote sensing data and Geographic Information Systems (GIS) was used to monitor hydrological drought and its impact on soil and the environment. Among the most important indices used were the Normalized Difference Vegetation Index (NDVI), which assesses vegetation health and degradation due to drought, and the Moisture Stress Index (MMSI), which detects changes in soil and plant moisture content. These indices enabled the classification of soil and identification of the most degraded and most fertile areas based on water deficit variables. The results demonstrated that spectral indices are effective tools for assessing soil health, allowing for the monitoring of spatial and temporal changes. This provides a foundation for making sustainable decisions in natural resource management. The study found that the NDVI index accurately reflects vegetation vitality, while CI and BSCI help evaluate soil's physical and chemical properties. Additionally, the MMSI index effectively determined soil moisture levels. This research highlights the importance of spectral indices in offering proactive solutions to mitigate water deficit impacts and achieve environmental and economic sustainability in Baiji.